Cover Image. Issue 11 (6th December 2020) - Smedile, Francesco; Giordano, Giovanni; Pariante, Rosanna; Padua, Mariangela; Bagolan, Pietro; Longo, Daniela; Sgrò, Stefania; Picardo, Sergio
Abstract : The cover image is based on the Short Report Management of accidental lumbar epidural catheter breakage in a 5‐month‐old infant by Francesco Smedile et al., https://doi.org/10.1111/pan.14022